America : - Tindall, George Brown (W. W. Norton, 1999)
A bestseller in its previous editions, now redesigned in a larger size with two-color maps. The authors look at how colonial taverns not only served as places to socialize but also became hotbeds for political action before the American Revolution; they explore how the rise of baseball served to equalize whites of different classes but exacerbated racial tensions through segregated leagues; and they explore the rise of rock and roll and the "youth culture" of the 1950s as a reaction to cultural conservatives.